2006
DOI: 10.2460/javma.228.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Long-term complications after phacoemulsification for cataract removal in dogs: 172 cases (1995–2002)

Abstract: Evaluation of breed and cataract hypermaturity may aid in the selection of patients. The increasing prevalence of postoperative complications with time indicated that longterm monitoring is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
179
6
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(204 citation statements)
references
References 30 publications
17
179
6
2
Order By: Relevance
“…With these results of humidity kept in mind, it can explain why corneal sensitivity values (filament length) obtained in the present study are lower than those obtained in previous studies (Barrett et al, 1991;Good et al, 2003;Dorbandt et al, 2017). Although some previous studies in humans and dogs demonstrated the analgesic action of flurbiprofen and ketorolac (Sigle and Nasisse, 2006;Maca et al, 2010), the present study suggests that the ophthalmic application of these two drugs do not promote analgesic activity on corneal nociceptor activity in healthy canine eyes. Another recent study (Dorbandt et al, 2017) also demonstrated a lack of analgesic activity after topical application of flurbiprofen to canine eyes.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…With these results of humidity kept in mind, it can explain why corneal sensitivity values (filament length) obtained in the present study are lower than those obtained in previous studies (Barrett et al, 1991;Good et al, 2003;Dorbandt et al, 2017). Although some previous studies in humans and dogs demonstrated the analgesic action of flurbiprofen and ketorolac (Sigle and Nasisse, 2006;Maca et al, 2010), the present study suggests that the ophthalmic application of these two drugs do not promote analgesic activity on corneal nociceptor activity in healthy canine eyes. Another recent study (Dorbandt et al, 2017) also demonstrated a lack of analgesic activity after topical application of flurbiprofen to canine eyes.…”
Section: Introductioncontrasting
confidence: 56%
“…Topical NSAIDS are primarily used for inflammatory ocular conditions such as the suppression of uveitis that may be present before and after intraocular surgery http://www.openveterinaryjournal.com R. Cantarella et al Open Veterinary Journal, (2017), Vol. 7(3): 254-260 ________________________________________________________________________________________________________ 255 (Giuliano, 2004;Sigle and Nasisse, 2006;Kim et al, 2010;Maca et al, 2010;Klein et al, 2011). Chen et al (1997) showed that the application of topical NSAID ophthalmic solutions effectively reduced corneal sensitivity as well as the sensitivity of polymodal nociceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Phacoemulsification normally reduces surgical trauma where access to the lens is gained through a small incision on the ocular surface (Pereira et al 1999, Özgen-cil 2005, Sigle & Nasisse 2006. Moreover, it allows the most efficient removal of the lens material, minimizing endothelial damage (Özgencil 2005, Sigle & Nasisse 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, phacoemulsification has been becoming a common surgical procedure for restoring vision in veterinary patients with cataract [9,12,19]. Postoperative pain can be caused by intraocular manipulations that irritate intraocular tissue and induce the subsequent inflammatory response in the veterinary patient undergoing ocular surgery including phacoemulsification [13].…”
mentioning
confidence: 99%